Inferior vena cava obstruction secondary to hepatic alveolar echinococcosis: a case report - Jingxin Yan (Egyptian Liver Journal)
Abstract Hepatic echinococcosis is a global zoonotic disease that typically manifests through direct invasion of the bile ducts and vascular structures of the liver, subsequently spreading to adjacent organs and tissues. Inferior vena cava syndrome resulting from compression of the hepatic vein and inferior vena cava by hepatic echinococcosis is exceedingly rare. Here, we report a case of a 53-year-old man presented with inferior vena cava obstruction and portal hypertension secondary to hepatic alveolar echinococcosis. The patient’s lesion was primarily located in segments S6/7 of the liver, with metastasis and invasion affecting the right kidney, thoracic 11-lumbar 1 vertebral bodies, and inferior vena cava. Radical surgery was not an option due to severe portal hypertension and deteriorating liver function, posing a significant threat to the patient’s life. Consequently, interventional treatments, including intrahepatic portosystemic shunt and hepatic venoplasty, were performed to reduce portal vein pressure, alleviate portal hypertension and inferior vena cava stenosis. Interventional treatments significantly could improve liver function, thereby facilitating future treatment options. Post-intervention follow-up revealed no recurrence of symptoms associated with inferior vena cava syndrome. However, the patient developed uremia due to renal involvement and was managed with dialysis. This article reported on the treatment process, and summarized treatment options for similar patients, providing valuable suggestions and references for clinical diagnosis and management of comparable cases in the future.